Formal Balance Assessment and Intervention in Patients With Newly Implanted Left Ventricular Assist Devices: A Retrospective Analysis. Issue 2 (April 2017) - Appel, Jessica; Vatwani, Archana; Sutton, Kristin; Hall, Amy; Russell, Stuart D.
Abstract : Purpose: The purpose of this study was to retrospectively review the implementation of a formal balance assessment and directed interventions in a sample of patients with newly implanted left ventricular assist devices (LVADs). Methods: Electronic medical records were reviewed in patients with newly implanted LVADs from January 2014 through August 2015. Patients were assessed using Tinetti Performance Oriented Mobility Assessment (Tinetti) and AM-PAC Inpatient Basic Mobility Short Form (AM-PAC). Patients participated in formal balance interventions. Data was analyzed using Microsoft Excel (Kirkland, WA) using a Student t test with 2-sided tail or paired t test, with a P -value of <.05 indicating statistical significance. Results: Of those patients included in the study, 94% of patients demonstrated initial fall risk, and 82% of patients demonstrated initial high fall risk. The initial Tinetti score was 13.7 (SD 7.2), increasing to 24.5 (SD 4.0) ( P < .001) after intervention. Patients with high fall risk had an average length of stay of 27.36 days (SD 24.42 days) compared with those with lower fall risk with an average length of stay of 19.67 days (SD 6.55 days) ( P = .62). Conclusions: A balance deficit was observed in patients with newly implanted LVADs. Following standardized intervention, deficits improve. These results warrant further exploration into proper dosing of intervention, additional outcome measures, and further research development.